AL-MUBASYAROH METHOD IN LEARNING ARABIC LANGUAGE IN MADRASAH IBTIDAIYAH - Nabilah, Syarotun; Ulin Nuha, Muhammad Afton (Fashohah : Jurnal Ilmiah Pendidikan Bahasa Arab, 2024)
The Arabic language education program has become part of improving the quality of Arabic language education that identifies with Islamic religion-based education in Indonesia. Success in the learning process depends on the procedures used by educators in learning activities. In this study will discuss the al mubasyaroh method which will be implemented in Arabic language education madrasah ibtidaiyah fourth, fifth and sixth grades, or high grades where in these classes students have gained basic knowledge of Arabic in grades one two and three, namely low grades. In the al- mubasyaroh method dominates Arabic language learning with speech to emphasize the mastery of Arabic word addition in everyday life. In the method of teaching Arabic as a direct language between educators and learners without using translation. Active participation of educators and learners becomes a reference for the success of the learning process.